Regiões de procedência de abacaxi para a Ceagesp de São Paulo e análises qualitativa, comparativa e das causas da valoração dos frutos - Almeida, Gabriel Vicente Bitencourt de [UNESP] (2014)
The objective of the thesis was divided into two parts or steps, both in order to understand and explain the dynamics of the pineapple market in Brazil's largest central wholesaler and measure seasonal and qualitative factors that lead to determining the wholesale price or wholesale value in São Paulo's market, a direct result of the acceptance of 'Perola' and 'Smooth Cayenne' cultivars, holding relevant production volume/share in Brazil. In the first part the data generated by the Market Information and Statistics System [Sistema de Informação e Estatística de Mercado (SIEM)] and the price quotation service of the General Warehouses Company of São Paulo [Companhia de Entrepostos e Armazéns Gerais de São Paulo (CEAGESP)], between the years 2007 and 2013, were analyzed and the results describe and analyze the seasonal behavior and price formation. It can be concluded that: the price variation of the 'Pearl' is a function of supply and demand, the alternation of various producing regions and climatic conditions, since higher temperatures proven to stimulate consumption. The seasonal variation in prices of 'Smooth Cayenne' is related to the quality of inflorescences and the lower supply of 'Pérola'. The objective of the second part was to determine, from pineapple inflorescences collected in São Paulo CEAGESP, witch are the most important quality characteristics for the acceptability of buyers and determining valuation; at the same time to verify and understand if the different origins differed or not significantly related to the attributes analyzed. For the 'Pérola' cultivar variables that showed the highest relationship with the wholesale selling price were, respectively, color, soluble solids (SS) and SS/TA ratio. The mass of the inflorescence was more relevant factor to the 'Smooth Cayenne'. The states whose pineapples 'Pérola' received the best relative prices alone were Goiás and ...